IMPLIKASI DINAMIKA KONSEP TERIKAT MASJID DENGAN MEMAKMURKANYA DIJAMIN SURGA DAN MANFAATNYA BAGI INTELEKTUAL MENURUT KONSEP SUNNAH - atnawi atnawi; mafruhah mafruhah (Fakultas Agama Islam Universitas Islam Madura, 2021)
Moslems have the place of worship as a place to bind God. The place of worship not only place of prater like is surau, langgar, and et cetera, but the main one is the mosque. the mosque as a place of worship and also a symbol of very dinamic moslem unity. Moslems are obliged to care about the mosque not only in the build, but it is very important to bound the mosque and always go to the sacred. This research is qualitative with sciemtific method that substance lies in the dynamics of bound mosque.. In this study, there is implication of dinamycs concept of bound of the mosque with this process of purpose. People who prosper the mosque include among people guaranted to go to heaven. Even prospering the mosque has many benefits both in the world and in the hereafter, especially for intelectual (academics). Means thus, the contribution of building mosque and pursuers it can happiness in the world and in the hereafter of heaven paradise